Cochlear Implantation in Adults With Single-sided Deafness: Outcomes and Device Use. Issue 3 (14th March 2021) - Deep, Nicholas L.; Spitzer, Emily R.; Shapiro, William H.; Waltzman, Susan B.; Roland, J. Thomas; Friedmann, David R.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To describe our experience with adults undergoing cochlear implantation (CI) for treatment of single-sided deafness (SSD). Study Design: Retrospective case review. Setting: Tertiary referral center. Patients: Fifty-three adults with SSD. Intervention(s): Unilateral CI. Main Outcome Measure(s): Speech perception testing in quiet and noise, tinnitus suppression, and device usage from datalogs. Results: The mean age at CI was 53.2 years (SD 11.9). The mean duration of deafness was 4.0 years (SD 7.8). The most common etiology was idiopathic sudden SNHL (50%). Word recognition improved from 8.7% (SD 15) preoperatively to 61.8% (SD 20) at a mean follow-up of 3.3 years (SD 1.8) ( p  < 0.0001). Adaptive speech recognition testing in the "binaural with CI" condition (speech directed toward the front and noise toward the normal hearing ear) revealed a significant improvement by 2.6-dB SNR compared to the preoperative unaided condition ( p  = 0.0002) and by 3.6-dB SNR compared to when a device to route sound to the contralateral side was used ( p  < 0.0001). Tinnitus suppression was reported to be complete in 23 patients (43%) and improved in 20 patients (38%) while the device was on. The addition of the CI did not lead to a decrement in hearing performance in any spatial configuration. Device usage averaged 8.7 (SD 3.7) hours/day. Conclusions: Cochlear implantation in adult SSD patients can suppress tinnitus and achieve speech perception outcomes comparable with CI in conventional candidates. Modest improvements in spatial hearing were also observed and primarily attributable to the head shadow effect. Careful patient selection and counseling regarding potential benefits are important to optimize outcomes.